Management of pregnant women with cardiac disease at a tertiary referral hospital: a one year review. (18th April 2012) - Tripathi, P; O'Connor, K; McCreath, B; Walker, H; Brennand, J
Abstract : Aim: To assess standard of care, patterns of referral and categories of cardiac disease at our combined obstetric cardiac clinic (COCC) and describe obstetric, anaesthetic and neonatal outcomes in these women. Methods: Retrospective case note review of all cases seen between January 2010- January 2011. Results: A total of 92 women were seen and 89 case records obtained. Of these, 34 women who were deemed 'moderate risk' and delivered at the tertiary unit were analysed in detail. 62% women had congenital and 38% acquired cardiac disease. Septal defects were the commonest congenital defect (20.5%) followed by TGA and aortic valve disease (15% each). Commonest acquired disease was arrhythmia (32%). Just under 60% women were pre-assessed at the anaesthetic clinic antenatally. Commonest anaesthetic for delivery overall was combined spinal epidural (CSE). 23% suffered a cardiac complication and 9% obstetric complication during their pregnancy. This included 5 women who recorded a decline in their NYHA status in later pregnancy. While three of them had an elective caesarean for deterioration in cardiac function at less than 37 weeks, one had it at > 37 weeks and the fifth woman had a normal delivery at 38+ weeks. The anaesthetic for all these caesareans was CSE. No major neonatal complications were recorded. Conclusion: The level of care was satisfactory although need for better documentation of neonatal outcomes was recognised. The outcomes were largely similar to a previously concluded audit in our unit and comparable to the larger studies in a similar cohort of women.